2019 IEEE European Symposium on Security and Privacy Workshops (EuroS&PW) 2019
DOI: 10.1109/eurospw.2019.00041
|View full text |Cite
|
Sign up to set email alerts
|

Empirically Analyzing Ethereum's Gas Mechanism

Abstract: Ethereum's Gas mechanism attempts to set transaction fees in accordance with the computational cost of transaction execution: a cost borne by default by every node on the network to ensure correct smart contract execution. Gas encourages users to author transactions that are efficient to execute and in so doing encourages node diversity, allowing modestly resourced nodes to join and contribute to the security of the network.However, the effectiveness of this scheme relies on Gas costs being correctly aligned w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It provides a run-time environment that is isolated from the network to execute the smart contract code. Computation in EVM [28] is essentially bounded by transaction fees. Smart contracts contain ethers (a type of cryptocurrency) as their balance.…”
Section: Ethereum Blockchain Smart Contractmentioning
confidence: 99%
See 1 more Smart Citation
“…It provides a run-time environment that is isolated from the network to execute the smart contract code. Computation in EVM [28] is essentially bounded by transaction fees. Smart contracts contain ethers (a type of cryptocurrency) as their balance.…”
Section: Ethereum Blockchain Smart Contractmentioning
confidence: 99%
“…Ethers can be sent to other contracts for executing the smart contract. It is a very crucial task because any type of vulnerability can be the reason for the loss of millions of Ether [28]. A smart contract cannot be changed after the deployment [29] on the blockchain due to the immutable [30] nature of the blockchain.…”
Section: Ethereum Blockchain Smart Contractmentioning
confidence: 99%
“…In the literature there are some proposals that aim to measure the CPU usage for individual operation codes that reside in the EVM. These proposals include OpBench framework 31,32 as well as the work presented in Chen et al, Perez and Livshits, and Yang et al 33–35 Our measurement approach is different from these approaches found in the literature. We measure the CPU usage for smart contracts at the transaction level, while these proposals focus on measuring the CPU usage at the operation code level.…”
Section: Related Workmentioning
confidence: 99%
“…Again, there is not automation and those patterns are manually identified. There is recent work that experimentally proves that the gas model for some EVM instructions is not correctly aligned with respect to the observed computational costs in real experiments [26], and that these misalignments can lead to gas-related attacks [22]. Our work is parametric on the gas model used, and new adjustments in the gas model of Ethereum are integrated in our optimizer by just updating the cost for the corresponding modified instructions in our implementation.…”
Section: Related Workmentioning
confidence: 99%